The Quality of Functional Movements and the Back Squat in Amateur and Professional Bodybuilders - VERONIKA ILJINAITĖ; LAIMONAS ŠIUPŠINSKAS; KRISTINA BERŠKIENĖ (North American Sports Medicine Institute, 2024)
# Background It is important to assess the quality of fundamental movements, to discover deficits, evaluate mobility, balance, and stability, and identify movement dysfunction and asymmetries. However, little research has been performed on the assessment of fundamental movements with bodybuilders. # Purpose The purpose of this research was to examine the quality of professional and amateur bodybuilders' functional movements and the quality of the back squat performance. A secondary purpose was to discern whether greater experience in bodybuilding was associated with better scores on the back squat assessement (BSA). # Study design Cross-Sectional Cohort # Methods Twenty-six athletes were recruited to participate. The group of professional bodybuilders consisted of five men and six women, a total of 11 athletes. The group of amateur bodybuilders consisted of seven men and eight women, a total of 15 athletes. The Functional Movement Screen™ (FMS™) was used to assess the seven included fundamental patterns that evaluate an individual's neuromuscular control, mobility, balance, and stability. The BSA was used to assess the quality of movement, dysfunction, deficit, or compensation during the squat exercise. Statistical analyses applied non-parametric tests (Wilcoxon, Mann-Whitney U, and Friedman's) for dependent and independent samples, with significance set at p\<0.05, and the Spearman correlation coefficient and Chi-square test were used to assess relationships between quantitative and qualitative variables. # Results Overall, athletes with a higher total FMS™ score performed better on the BSA as well. The professional athletes scored 2.58 points higher than the amateurs on total FMS™ scores (p\<0.001). Professional athletes scored better on the BSA than amateurs (p\<0.001). A statistically significant, positive moderate correlation was revealed between the FMS™ total score and the squat total score (r=0.68; p=0.005). # Conclusions A higher FMS™ score in bodybuilders is associated with a higher BSA score. Professional bodybuilders have higher FMS™ scores and higher BSA scores than amateurs. Greater experience in bodybuilding is associated with the compliance with several BSA criteria: trunk position, frontal knee alignment, tibial translation angle, foot position in all three back squat variations with different external loads, and descent with the training weight. # Level of Evidence 3b